Convective and microwave drying kinetics and modeling of tomato slices, energy consumption, and efficiency. (21st June 2022) - Guemouni, Sara; Mouhoubi, Khokha; Brahmi, Fatiha; Dahmoune, Farid; Belbahi, Amine; Benyoub, Cylia; Adjeroud‐Abdellatif, Nawel; Atmani, Karim; Bakhouche, Hicham; Boulekbache‐Makhlouf, Lila; Madani, Khodir
Abstract: This investigation presented presents the drying characteristics, and aimed to predict the drying kinetics of tomato slices ( Lycopersicon esculentum MILL.) using convection and microwave methods. Hot air drying was carried out in a ventilated oven at 50, 60, 80, and 100°C temperatures and microwave drying was performed in domestic microwave using 300, 500, 800, and 900 W powers. Twenty‐two mathematical models were undertaken to predict the drying kinetics and the best model was chosen based on the highest R 2 values and the lowest root mean square error (RMSE) and χ 2 values. Drying kinetics, drying rate variation, diffusivity and energy consumption of both methods were evaluated. Fernando and Amarasinghe model and Sledz model were the best models for convective and microwave drying processes, respectively. Effective moisture diffusivity varied from 0.28 × 10 −9 to 2.81 × 10 −9 and from 1.32 × 10 −9 to 21.52 × 10 −9, while the activation energy was 27.64 kJ/mol and 5.71 W/g for convective and microwave drying processes, respectively. The energy consumption increases with increasing temperature or power, the reverse was observed for energy efficiency. Microwave drying process has the advantage of drying time reduction, low‐energy consumption, and high‐drying efficiency at a moderate high‐power level (900 W). Hence, it is recommended to apply this innovative process for drying tomato slices. Abstract : In this study by using more than 20 models, for the first time, we demonstrated that microwave‐assisted drying of tomato slices was more effective than forced convection drying. It revealed a shorter drying time, high‐drying rates, and high diffusivity with low‐energy consumption.